Growth and development of children under 5 years of age with tetralogy of Fallot in a Chinese population - Xin Li (Nature Portfolio, 2021)
Abstract Congenital Heart Defects (CHDs) are associated with different patterns of malnutrition and growth retardation, which may vary worldwide and need to be evaluated according to local conditions. Although tetralogy of Fallot (TOF) is one of the first described CHDs, the etiology outcomes in growth and development of TOF in early age child is still unclear in most cases. This study was designed to investigate the growth retardation status of Chinese pediatric TOF patients under 5 years old. The body height, body weight and body mass index (BMI) of 262 pediatric patients (138 boys and 124 girls) who underwent corrective surgery for TOF between 2014 and 2018 were measured using conventional methods. The average body height, body weight and BMI of the patients were significantly lower than WHO Child Growth Standards, while the most affected was body height. Meanwhile, higher stunting frequency and greater deterioration of both the body height and weight happened in elder age (aged 13–60 months) rather than in infant stage (aged 0–12 months) among these patients. Our results confirmed that intervention should be given at early age to prevent the growth retardation of TOF patients getting severer.